2020
DOI: 10.3390/nu12020541
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition at Admission Predicts In-Hospital Falls in Hospitalized Older Adults

Abstract: Malnutrition leads to poor prognoses, including a predisposition to falls. Few studies have investigated the relationship between malnutrition and falls during hospitalization. This study aimed to determine malnutrition’s association with falls during hospitalization. A retrospective observational study was conducted. Patients aged ≥65 years that were admitted to and discharged from a university hospital between April 2018 and March 2019 were examined. Patients with independent basic activities of daily living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
1
13
0
4
Order By: Relevance
“…A lower MNA-SF score at admission was also associated with increased risk of being a faller in orthogeriatric patients. Our results also confirm the relationship between nutritional status and falls in orthogeriatric patients in other clinical settings [ 28 , 29 ]. A fall represents an adverse outcome that could influence the rehabilitation process with worse functional recovery, increasing the length of stay and reducing the probability of being discharged at home [ 52 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A lower MNA-SF score at admission was also associated with increased risk of being a faller in orthogeriatric patients. Our results also confirm the relationship between nutritional status and falls in orthogeriatric patients in other clinical settings [ 28 , 29 ]. A fall represents an adverse outcome that could influence the rehabilitation process with worse functional recovery, increasing the length of stay and reducing the probability of being discharged at home [ 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…Malnutrition is also related to higher incidence of falls and risk of falling in hospitalized and community-dwelling older adults [ 28 , 29 ]. These events can lead to many adverse consequences in this population, such as functional decline, increased morbidity and even death [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the risk of falls increases up to 8.4% and 6.2% in geriatric and internal medicine wards, respectively, and the global fall rate rises up to 31.6% up to 39.5% in patients ≥80 years [65]. Old patients with malnutrition and independent activities of daily living (ADL) were recently reported with a 2.7 higher risk of in-hospital falls [66]. In a 5-year observational study, malnourished patients showed an 8-times higher risk of harmful falls during hospitalization as compared to well-nourished patients [67].…”
Section: Malnutrition Falls and Other Complications Of Hospitalizationmentioning
confidence: 99%
“…2,26 Although many clinical studies in Japanese individuals have reported an association of ESPEN criterion malnutrition with clinical outcomes, no report has examined whether the cut-offs for BMI and lean body mass index, components of the ESPEN criterion malnutrition diagnosis, are optimal cut-offs for Japanese people. [27][28][29] GLIM-defined malnutrition requires the presence of phenotypic and etiologic criteria, whereas ESPEN-defined malnutrition does not involve etiologic factors. Further studies must be carried out to determine the validity of GNRI <96 points in diagnosing GLIM-defined malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we only used the ESPEN criteria in diagnosing malnutrition, although the latest diagnostic criteria from GLIM had been published 2,26 . Although many clinical studies in Japanese individuals have reported an association of ESPEN criterion malnutrition with clinical outcomes, no report has examined whether the cut‐offs for BMI and lean body mass index, components of the ESPEN criterion malnutrition diagnosis, are optimal cut‐offs for Japanese people 27–29 . GLIM‐defined malnutrition requires the presence of phenotypic and etiologic criteria, whereas ESPEN‐defined malnutrition does not involve etiologic factors.…”
Section: Discussionmentioning
confidence: 99%